The effect of different wall materials (Sodium alginate, whey protein isolate, Kappa-carrageenan and Citrus pectin) on the viability and stability of free and encapsulated Lactobacillus acidophilus under hostile condition - Aleena Naaz; Muhammad Afzaal; Farhan Saeed; Aasma Asghar; Aftab Ahmed; Atif Liaqat; Rabia Iqbal; Suliman Yousef Alomar; Asad Nwaz; Degnet Teferi Asres (Cogent Food & Agriculture)
The aim of this study was to investigate the effects of different encapsulation materials, namely Sodium alginate, Whey protein isolate, Kappa-carrageenan, and Citrus pectin, on the viability and stability of probiotics. The probiotics were encapsulated using the internal gelation method and the resulting microbeads were measured for their size and encapsulation efficiency. The viability of Lactobacillus acidophilus, both free and encapsulated, was evaluated under gastric and intestinal conditions. The results revealed that all wall materials had a significant impact (p < 0.05) on the viability of probiotics under different conditions. The highest encapsulation efficiency was observed for whey protein isolate (97%), followed by K-carrageenan (95.8%) and citrus pectin (95%). Encapsulation with WPI and SA resulted in the highest survival rates of probiotics compared to free cells during exposure to SGF and SIF. Similarly, the hydrogel-encapsulated probiotics demonstrated better survival and stability in yogurt during storage. The statistical results indicate that microencapsulation enhances the survival of probiotics in yogurt during storage days.